Sustainability Report and Firm Value: an Evidence from Indonesia - Kenneth Sahetapy (Sekolah Tingg Ilmu Ekonomi Y.A.I Jakarta - Indonesia, 2023)
The reporting of sustainability reports remains to be voluntary in Indonesia. Therefore, there are questions regarding whether the market values the report. This research attempts to answer this question by examining the impact of firms’ sustainability reports on their firm value. This research delves further into the topic of how firms’ sustainability reports affect the value of the firm. While prior research has been done in advanced countries and countries with high reporting rates, this research analyses the effect of how firms’ sustainability reports affect firm value in a developing country with a low reporting rate. To test the hypothesis, this research uses 100 of the biggest companies in Indonesia as the sample and conducts an Ordinary Least Square regression analysis. The results indicate that the market gave a positive value to a sustainability report. This result provides an argument that companies should report their sustainability performance through a sustainability report because this information is valued by the market.